2011
DOI: 10.1259/bjr/24661484
|View full text |Cite
|
Sign up to set email alerts
|

MRI in lung cancer: a pictorial essay

Abstract: ABSTRACT. Imaging studies play a critical role in the diagnosis and staging of lung cancer. CT and 18-fluorodeoxyglucose positron emission tomography CT (PET/CT) are widely and routinely used for staging and assessment of treatment response. Many radiologists still use MRI only for the assessment of superior sulcus tumours, and in cases where invasion of the spinal cord canal is suspected. MRI can detect and stage lung cancer, and this method could be an excellent alternative to CT or PET/CT in the investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 17 publications
(18 reference statements)
0
45
1
2
Order By: Relevance
“…Above all, the T stage of a tumor determinates its resectability (19,20). The ability to differentiate between stages T3 and T4 is critical for any cross-sectional imaging modality, because T4 tumors are widely considered not resectable.…”
Section: Resectability and T Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, the T stage of a tumor determinates its resectability (19,20). The ability to differentiate between stages T3 and T4 is critical for any cross-sectional imaging modality, because T4 tumors are widely considered not resectable.…”
Section: Resectability and T Stagingmentioning
confidence: 99%
“…Despite suggestions of using short TI inversion recovery or T2-weighted black-blood imaging for the assessment of small mediastinal nodes, MR has not gained widespread clinical acceptance for N staging of lung cancer (10,12,20,22). For PET/MR, Fraioli et al reported good accordance of PET/MR and PET/CT but did not provide data on the accuracy of PET/MR in comparison with PET/CT (6).…”
Section: N Stagingmentioning
confidence: 99%
“…As recent advances in morphological and functional MRI allow for detection, characterization and staging of pulmonary nodules with a diagnostic quality equivalent to that of CT and positron emission tomography (PET)-CT (Hochhegger et al 2011), and given the ABC’s ability to arrest respiration at an individually defined and reliably reproducible inhaled or exhaled air volume, we anticipated that MR and CT images would match for the same ABC settings and patient positioning.…”
Section: Discussionmentioning
confidence: 99%
“…24 Magnetic resonance imaging for baseline staging or assessment of treatment response in lung cancer is still investigational. However, higher magnetic field strengths (3 T), development of faster imaging sequences, advancements in digital signal processing, utilization of respiratory and cardiac gating, and better MRI contrast agents have all improved the utility of MRI for lung cancer staging.…”
Section: Pet Response Criteria In Solid Tumorsmentioning
confidence: 99%